La violencia selectiva y colectiva contra civiles y el escalamiento del conflicto armado: el caso de la Unión Patriótica en Colombia (2021)
Although different studies have analyzed the causes of violence against civilians in civil wars, few investigations have examined the effects or consequences of violence against particular segments of the population in the dynamics of civil war, that is, on the warlike behavior of fighting groups. Taking the Colombian armed conflict as a frame of reference, this document analyzes the consequences of selective and collective violence against the political party Unión Patriótica in the escalation of the conflict between 1985 and 1995. Using the information at the municipal level, it is found that increases in lethal violence against members and sympathizers of the political party that emerged from the peace negotiations (1984-1987) with the FARC-EP guerrilla group, generated increases in selective assassinations attributed to the FARC-EP, but not increases in other variables such as military actions, terrorist attacks or raiding towns. The increases in selective assassinations as a consequence of what happened with the UP were in the short-term and did not modify at the local level the long-term dynamics of the confrontation between the FARC-EP against the State. Qualitative evidence suggests that these short-term increases in targeted killings were due more to retaliatory actions against potential perpetrators and strategic actions. The generalized method of moments (GMM) is used to solve the potential problems of causality and omitted variables that can skew the econometric results.